Virtually Standing Up or Standing By? Correlates of Enacting Social Control Online - Costello, Matthew; Hawdon, James; Cross, Amanda (International Journal of Criminology and Sociology, 2016)
Research has consistently established the robustness of the bystander effect, or the tendency of individuals to not intervene on behalf of others in emergency situations. This study examines the bystander effect in an online setting, focusing on factors that lead individuals to intervene, and therefore enact informal social control, on behalf of others who are being targeted by hate material. To address this question, we use an online survey (N=647) of youth and young adults recruited from a demographically balanced sample of Americans. Results demonstrate that the enactment of social control is positively affected by the existence of strong offline and online social bonds, collective efficacy, prior victimization, self-esteem, and an aversion for the hate material in question. Additionally, the amount of time that individuals spend online affects their likelihood of intervention. These findings provide important insights into the processes that underlie informal social control and begin to bridge the gap in knowledge between social control in the physical and virtual realms.